2022
DOI: 10.1007/s10664-022-10126-5
|View full text |Cite
|
Sign up to set email alerts
|

On the adequacy of static analysis warnings with respect to code smell prediction

Abstract: Code smells are poor implementation choices that developers apply while evolving source code and that affect program maintainability. Multiple automated code smell detectors have been proposed: while most of them relied on heuristics applied over software metrics, a recent trend concerns the definition of machine learning techniques. However, machine learning-based code smell detectors still suffer from low accuracy: one of the causes is the lack of adequate features to feed machine learners. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Code smells indicate that basic implementation principles were not followed in source code [1]. The code smell signifies the presence of a wide range of quality issues in the software.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Code smells indicate that basic implementation principles were not followed in source code [1]. The code smell signifies the presence of a wide range of quality issues in the software.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation, design, and architecture are the Detecting Security Bad Smells of Software by using Data Mining main subcategories that fall under the code smell in Java [2]. Some developers apply sub-optimal implementation decisions, negatively affecting the overall maintainability of software [1]. Many studies have shown how code smells are introduced and evolved and their influence on program comprehension [3].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the properties of object-oriented systems (encapsulation, data abstraction, and modularity) and quality, there is a need to detect code smells in advance. 60,61 The large numbers of code smell detected by existing tools and approaches make it troublesome for a software developer to choose the order in which the detected code smells should be refactored. The developers do not have sufficient time to refactor every code smells.…”
Section: Alternative Classes With Different Interfacesmentioning
confidence: 99%
“…The popularity of Static analysis tools adoption is increasing over the years creating a humus layer for the research. In this section, we report the relevant work on static analysis tools focusing on their usage [44], [45], [12], [18], rules and the detected problems [46].…”
Section: Related Workmentioning
confidence: 99%
“…Examples of such studies include comparisons of tools in terms of capability [14], detection agreement, and precision [15]. Other studies compared specific aspects detected by the tools, such as security [16] or concurrency defects [17], [18].…”
Section: Introductionmentioning
confidence: 99%